Surveillance colonoscopy for Lynch syndrome in the Northern Cape: Does direct contact improve compliance? - Coccia, Anna Claudia (Division of General Surgery, 2019)
Introduction The Annual Northern Cape Colonoscopy Outreach program provides surveillance colonoscopy to high–risk individuals known with Lynch Syndrome along the west coast and in the Northern Cape Province of South Africa. There are currently over 100 known mutation positive individuals. Surveillance colonoscopies are performed annually in August/September, and are preceded a by a preparation visit approximately 6-8 weeks prior. The aim of the preparation trip has been to directly impart information, regarding preparation and importance of attendance, to individuals required to attend annual surveillance. During the preparation trip an attempt is made to reach all individuals scheduled for surveillance but due to the vastness of the Northern Cape inevitably every year some areas are not visited. It has been noted that over the past few years fewer than 25 % of the total participants obtained 100 % adherence to surveillance. Objectives The primary objective of this study is to determine whether there is a need for a yearly colonoscopy preparation visit to high–risk individuals in the Northern Cape. The study determines if direct interaction with patients prior to surveillance colonoscopy will significantly impact attendance and adequacy of bowel preparation. Methods Seventy-eight individuals known with a genetic mutation for Lynch syndrome were enrolled in this randomised crossover trial spanning two years of surveillance. The control group (Group A) of individuals had bowel preparation and instructions forwarded to their local clinics and distributed to them via clinic or hospital staff. The test group (Group B) of individuals were personally visited and provided with instructions and bowel preparation by the research team. A measurement of attendance at surveillance colonoscopy as well as cleanliness of the colon was recorded. The study spanned two years of colonoscopy surveillance, July 2014 to September 2015, with a crossover of the control and test groups. Results The study cohort consisted of 28 (36%) male and 50 (64%) female participants with a median age of 39.5 years. Groups A and B consisted of 38 and 40 participants respectively. In September 2014 thirty-six (46.2%) participants presented for annual surveillance colonoscopy, 19 (50%) from the control group (Group A) and 17 (42.5%) from the intervention group (Group B). In 2015 there were 41 (53%) compliant individuals; this included 21 (55%) individuals receiving a preparatory direct contact visit (Group A), and 20 (50%) individuals from the 2015 control group B. Following exclusion of carry-over and period effect, the study intervention was found not to significantly impact attendance (p-value = 0.853). Superior attendance was noted in individuals with prior compliance to surveillance (p-value = 0.001). Conclusions Direct interaction with known Lynch syndrome individuals prior to annual surveillance colonoscopy has not shown to positively impact attendance. Interaction and counselling should focus on individuals identified to be defaulting surveillance.